Prokaryotic expression of the coat protein gene of Odontoglossum ringspot virus, preparation and application of its polyclonal antibodies - ZHANG Jie; MENG Chun-mei; RONG Song; ZHANG Chao; HONG Jian; WU Jian-xiang (浙江大学学报. 农业与生命科学版)
Odontoglossum ringspot virus (ORSV) is one of the most prevalent orchid viruses. The 477 bp coat protein gene (CP) of ORSV was cloned from the virus infected orchid samples using RT-PCR, and subcloned into a prokaryotic expression vector pET-32a. The recombinant prokaryotic expression vector (pET-32a-CP) was used to transform Escherichia coli BL21 (DE3). An about 37 ku thioredoxin A (TrxA) fusion protein was obtained with IPTG induction and Ni2+-NTA affinity column purification. The purified recombinant protein was used to immunize rabbits for production of polyclonal antibodies against the coat protein of ORSV. Using the polyclonal antibodies, an immunocapture RT-PCR and a dot-blot ELISA were established for reliable, sensitive and specific detection of ORSV. The two detection methods utilizing the prepared polyclonal antibodies provide a base for the diagnosis of the ORSV disease, the production of virus-free seedlings and antivirus breeding of the orchid.